Semiclassical modeling of high-order harmonic generation driven by an elliptically polarized laser field: the role of recolliding periodic orbits. (13th January 2017) - Abanador, P M; Mauger, F; Lopata, K; Gaarde, M B; Schafer, K J
Abstract: We model high-order harmonic generation (HHG) from an argon atom driven by an elliptically polarized laser field, using classical electron trajectories that are initialized from a discrete set of microcanonical distributions. Analysis of the returning trajectories reveals that when the atomic potential is accounted for, there are two possible ionization pathways leading to the same photon energy for both the short and the long trajectories found in the recollision model of HHG. We also demonstrate that the threshold ellipticity, a measure of the sensitivity to ellipticity, decreases as the harmonic order increases for both short and long trajectories, in qualitative agreement with recent experimental results (Larsen et al 2015 arXiv:1506.08660 ). We use a nonlinear dynamical analysis to show that this behavior is regulated by a set of recolliding periodic orbits (RPOs) that survive at ellipticities greater than 0.2 and can therefore drive the recollision dynamics even at relatively high ellipticity. The connection between the threshold ellipticity dependence we find and RPOs means that the effect should be general.